A Sub-spectrum Sensing Scheme Based on Reputation in Cognitive Radio Networks - Hongning Li; Qingqi Pei; Xiaohong Jiang; Rui Liang; Peng Geng (2010 International Conference on Computational Intelligence and Security, 2010)
With the existing Cognitive Radio Networks development, we present a sub-spectrum sensing scheme based on reputation, which takes advantage in energy consumption, security and fairness from spectrum sensing, data fusion and spectrum allocation by classifying users and spectrum bands reasonably. The analysis shows that the sub-spectrum sensing scheme can save energy and defense SSDF attacks effectively.